Xanthohumol inflammatory factor production and angiogenesis are inhibited by xanthohumol in breast cancer xenografts. - Monteiro, Rosário (2008)
Xanthohumol (XN), a natural polyphenol present in beer, is known to exert anti-cancer effects. However, its precise mechanisms are not yet clearly defined. The aim of this study was to investigate the effect of oral administration of XN in breast cancer xenografts in nude mice. Proliferation and apoptosis were first examined in MCF7 cell cultures after incubation with XN by trypan blue exclusion assay, [3H]-thymidine incorporation, KI67 immunostaining and TUNEL. Morphological and histological characteristics of tumours from XN-treated or control (vehicle-treated) mice were compared. Immunohistochemistry for proliferative, inflammatory and endothelial cell markers was performed and activation of nuclear factor kappa B (NFkappaB) pathway was assessed by ELISA. In vitro MCF7 cell proliferation decreased in a dose-dependent manner. Oral administration of XN to nude mice inoculated with MCF7 cells resulted in central necrosis within tumours, reduced inflammatory cell number, focal proliferation areas, increased percentage of apoptotic cells and decreased microvessel density. Anti-angiogenic effects of XN were further confirmed by immunoblotting for factor VIII expression in XN-treated tumours as compared to controls. Decreased immunostaining for NFkappaB, phosphorylated-inhibitor of kappa B and interleukin-1beta were also observed as well as a significant decrease in NFkappaB activity to 60% of control values. These novel findings indicate that XN is able to target both breast cancer and host cells, namely inflammatory and endothelial cells, suggesting its potential use as a double-edge anti-cancer agent.